Financial applications on fractional Levy Stochastic processes - Abdullah Aljethi, Reem; Kılıçman, Adem (Multidisciplinary Digital Publishing Institute, 2022)
In this present work, we perform a numerical analysis of the value of the European style options as well as a sensitivity analysis for the option price with respect to some parameters of the model when the underlying price process is driven by a fractional Lévy process. The option price is given by a deterministic representation by means of a real valued function satisfying some fractional PDE. The numerical scheme of the fractional PDE is obtained by means of a weighted and shifted Grunwald approximation.